2013
DOI: 10.26719/2013.19.4.362
|View full text |Cite
|
Sign up to set email alerts
|

Relation between some haematological abnormalities, degree of immunosuppression and viral load in treatment-naïve HIV-infected patients

Abstract: This cross-sectional study at a teaching hospital in north-eastern Nigeria estimated the prevalence of anaemia, leukopenia and thrombocytopenia in treatment-naïve HIV-infected patients (177 males and 316 females), and the associations with virological and immunological markers. The overall prevalences of anaemia, leukopenia and thrombocytopenia were 49.5%, 5.5% and 4.5% respectively. The prevalence of anaemia was significantly higher in males than females (61.6% versus 42.7%), while the rates of leukopenia (5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
5
17
0
1
Order By: Relevance
“…This was probably due to improvement of hemoglobin concentration after antiretroviral therapy. This was in concordance with study conducted by Denue et al, [12] with mean hemoglobin value of 11.89±1.61g/dl in ART experienced patients and mean hemoglobin of 9.76±2.82g/dl in ART naïve patients. RBC indices: Mean value of MCV (mean corpuscular volume) in the present study was 83.31±7.30fl in treatment naïve HIV reactive patients and 89.40±8.34fl in patients on ART which was significantly higher (p value: 0.001).…”
Section: Evaluation Of Hematological Parameters Rbc Parameterssupporting
confidence: 93%
“…This was probably due to improvement of hemoglobin concentration after antiretroviral therapy. This was in concordance with study conducted by Denue et al, [12] with mean hemoglobin value of 11.89±1.61g/dl in ART experienced patients and mean hemoglobin of 9.76±2.82g/dl in ART naïve patients. RBC indices: Mean value of MCV (mean corpuscular volume) in the present study was 83.31±7.30fl in treatment naïve HIV reactive patients and 89.40±8.34fl in patients on ART which was significantly higher (p value: 0.001).…”
Section: Evaluation Of Hematological Parameters Rbc Parameterssupporting
confidence: 93%
“…4,6 Similar to previous studies by Bamlaku et al, 30 Denue et al, 31 Yakubu et al, 32 Ibrahim et al 33 they reported high prevalence of HIV infection among female. [31][32][33][34] This study supported the fact that Women are at a greater physiological risk of contracting HIV than men because women have a greater mucosal surface area exposed to pathogens and infectious fluid for longer periods during sexual intercourse 8 especially when exposed to unprotected heterosexual intercourse. Hormones such as progesterone are reported to be playing a role in a woman's biological vulnerability to HIV infection.…”
Section: Discussionsupporting
confidence: 76%
“…For instance, HIV infections cause alterations in the hematologic measures. Anaemia, leukopenia and thrombocytopenia are the most frequent hematologic manifestation in HIV-infected individuals (46,50,51). In addition, CD4 + T-helper lymphocyte counts are decreased in HIV infection; with lower CD4-counts exhibited in HIV-infected persons compared to HIV-uninfected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, possible that these derangements in the haematologic and immune profiles are exacerbated in HIV-positive substance users. (46,50,51). Immune status is an important marker of HIV disease progression and a strong determinant for the initiation of therapy (59).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation